2005
DOI: 10.1007/s10029-005-0055-1
|View full text |Cite
|
Sign up to set email alerts
|

Is there a risk of infertility after inguinal mesh repair? Experimental studies in the pig and the rabbit

Abstract: The implantation of a non-absorbable polypropylene mesh during hernia repair causes chronic foreign body reaction involving the surrounding tissue. In case of inguinal hernia repair using mesh techniques, the spermatic cord is potentially affected by this chronic inflammatory tissue remodeling. This effect has been investigated using standardized animal models (pig and rabbit). Fifteen adult male pigs underwent transinguinal preperitoneal implantation of a polypropylene mesh. The contralateral side with a Shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 19 publications
2
45
0
Order By: Relevance
“…4,5 A few animal studies on the inflammatory reaction of the mesh have been reported. Peiper et al 6 have found that inflammatory changes develop within 1-12 weeks. Another study reported increasing foreign body reaction to preperitoneal polyprolene mesh until the third week after implantation in pigs.…”
Section: Discussionmentioning
confidence: 98%
“…4,5 A few animal studies on the inflammatory reaction of the mesh have been reported. Peiper et al 6 have found that inflammatory changes develop within 1-12 weeks. Another study reported increasing foreign body reaction to preperitoneal polyprolene mesh until the third week after implantation in pigs.…”
Section: Discussionmentioning
confidence: 98%
“…The risk for infertility after mesh repair, as proposed by other authors 4,5,9,10 , has been regarded as an important question. Our results indicate that at the informed consent, the surgeon should not focus on the infertility problem.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast others have found proximal dilatation but no thickening of the wall of the vas deferens 2 . Decreased arterial perfusion in the testis 5,7 and spermatic venous thrombosis 4 have also been reported.. One study has shown beneficial effects on the integrity of the vas deferens when using lightweight mesh 3 whereas another study did not find any difference in inflammation and fibrosis comparing heavyweight with lightweight mesh 8 .…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations